2019
DOI: 10.1002/ptr.6255
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical and anti‐inflammatory studies of Dillenia suffruticosa leaves

Abstract: The Dillenia suffruticosa leaves (Dilleniaceae), a folk medicine recommended in Southeast Asia for treating inflammation, were phytochemically studied for the first time and assessed for suppression of λ‐carrageenan‐induced paw oedema in rats. The crude methanolic extract orally administered at 5,000 mg/kg, displayed no toxicity and at 250 to 1,000 mg/kg significantly suppressed the paw oedema. Two‐isolated triterpenoids, betulinic acid (1) and koetjapic acid (2) orally administered at 50 mg/kg, significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In macrophages, vitexin and isovitexin suppressed COX-1 and COX-2 mRNAs expression [ 103 , 115 117 ]. A recent study illustrated that vitexin displayed moderate inhibition more towards COX-2 compared to COX-1 enzyme, and the flavonoids interacted with hydrogen bonding more at the cyclooxygenase catalytic sites just like celecoxib, the known inhibitor [ 118 ]. An in silico study disclosed that vitexin had the highest fitness score against the COX-2 (63.49) and for enzyme COX-1 (60.43) and showed tactical hydrogen bonding against COX-1 and COX-2 [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…In macrophages, vitexin and isovitexin suppressed COX-1 and COX-2 mRNAs expression [ 103 , 115 117 ]. A recent study illustrated that vitexin displayed moderate inhibition more towards COX-2 compared to COX-1 enzyme, and the flavonoids interacted with hydrogen bonding more at the cyclooxygenase catalytic sites just like celecoxib, the known inhibitor [ 118 ]. An in silico study disclosed that vitexin had the highest fitness score against the COX-2 (63.49) and for enzyme COX-1 (60.43) and showed tactical hydrogen bonding against COX-1 and COX-2 [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular modeling suggested that KA can form stable complexes with these two proteins (Abubakar et al, 2019;Aswathy et al, 2021).…”
Section: Antic An Cer Comp Oundsmentioning
confidence: 99%
“…The exact molecular targets of KA have not been unambiguously identified. Two protein targets have been proposed based on molecular docking analyses: the enzyme COX‐2 (Abubakar et al, 2019) and protein mTOR (mammalian target of rapamycin) which is included in the mTORC1 complex and implicated in many signaling pathways (Figure 4). Molecular modeling suggested that KA can form stable complexes with these two proteins (Abubakar et al, 2019; Aswathy et al, 2021).…”
Section: Anticancer Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal side effects and cardiovascular thrombotic risk of celecoxib and other COX-2-selective drugs have also been reported [ 11 , 12 ]; thus, the use of celecoxib in patients with cardiovascular problems should be avoided [ 13 ]. As an alternative to coxibs, medicinal plants exhibit potent anti-inflammatory properties [ 14 ] due to a variety of their phytochemicals including phenolics [ 14 , 15 , 16 , 17 ], terpeniods [ 18 , 19 ], alkaloids [ 20 ] and flavonoids [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%